2009
DOI: 10.1097/pas.0b013e318180431d
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Alterations in Ductal Carcinoma In Situ-associated Myoepithelial Cells

Abstract: Recent molecular studies have indicated that ductal carcinoma in situ (DCIS)-associated myoepithelial cells (MECs) show differences from MECs in normal breast tissue. Such alterations may influence the progression of DCIS to invasive cancer. The purpose of this study was to investigate further phenotypic alterations in DCIS-associated MECs. Paraffin sections of 101 cases of DCIS (56 without and 45 with associated invasive carcinoma) were immunostained for 7 MEC markers: smooth muscle actin, smooth muscle myosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 21 publications
5
65
0
5
Order By: Relevance
“…30,31 Furthermore, there is also recent evidence that even the myoepithelial cells that are present around DCIS showed phenotypic alternations when compared with those lining normal ductal lobular units, and this may also have a role in the invasiveness of DCIS. 32 The current series also showed the absence of cancerization of the lobules by the DCIS in the biopsy to be another predictor for invasion. Lobular extension has been shown to be a significant predictor for invasion, 21 and when the size is 40.4 cm.…”
supporting
confidence: 55%
“…30,31 Furthermore, there is also recent evidence that even the myoepithelial cells that are present around DCIS showed phenotypic alternations when compared with those lining normal ductal lobular units, and this may also have a role in the invasiveness of DCIS. 32 The current series also showed the absence of cancerization of the lobules by the DCIS in the biopsy to be another predictor for invasion. Lobular extension has been shown to be a significant predictor for invasion, 21 and when the size is 40.4 cm.…”
supporting
confidence: 55%
“…Recently, absence of a myoepithelial cell layer has also been observed in some metaplastic apocrine glands [2,3]. Various studies have shown phenotypic alterations in ME cells associated with benign and in-situ lesions as compared to normal breast [4][5][6][7][8]. The interactive relationship between myoepithelial and luminal cells appears to be complex, with the integrity of the basement membrane being of prime importance in preventing malignant transformation [1,[6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, whether or not absence of myoepithelial cells in neoplastic lesions of the breast necessarily equates with stromal invasion has been controversial. This applies especially to encapsulated papillary carcinoma [2][3][4][5]. The role of ME cells in tumorigenesis has been the focus of much research in recent years [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Altered expression of these markers has been observed in the myoepithelial cells of DCIS lesions. Hilson et al were the first to report reduced staining intensity of DCIS-associated myoepithelial cells with various myoepithelial cell markers, lending support to the idea that these myoepithelial cells are phenotypically abnormal [42]. These authors also found that SMMHC, CD10 and CK 5/6 have lower sensitivity for DCISassociated myoepithelial cells than do SMA, p63 and calponin [42].…”
Section: The Transition From Dcis To Invasive Carcinomamentioning
confidence: 92%
“…Hilson et al were the first to report reduced staining intensity of DCIS-associated myoepithelial cells with various myoepithelial cell markers, lending support to the idea that these myoepithelial cells are phenotypically abnormal [42]. These authors also found that SMMHC, CD10 and CK 5/6 have lower sensitivity for DCISassociated myoepithelial cells than do SMA, p63 and calponin [42]. At our institution, we used two of the most common markers, p63 and calponin, in a large series of DCIS cases which revealed heterogeneous expression of these myoepithelial markers [ Figure 2].…”
Section: The Transition From Dcis To Invasive Carcinomamentioning
confidence: 93%